Isolation and identification of plastic degrading microorganism - Lee, Kwon Jun (2021)
Increased usage of plastic is leading to plastic pollution in the environment. Whilst plastics are believed to be non-biodegradable, it is believed that with long exposure to the environment, the microbiome in the environment may evolve to metabolise plastic. Many genera of microbes have been isolated and tested for degradation of polyethylene terephthalate and polystyrene however, deeper understanding of the mechanism and the demand for novel plastic degrading microorganisms is higher than ever. In this work, TPA degrading Streptomyces sps. was isolated from soil samples collected near human sewage treatment plant by utilizing selective enrichment on the isolates. Identification of the strain was done using molecular approaches and phenotypic assays showed the plastic degrading potential of the isolate. Metabolic profiles of the isolate were assessed by LCMS with the results indicating difference in the culture grown in protocatechuic acid and terephthalic acid.